2020
DOI: 10.15761/cogrm.1000301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female body mass index on the outcome of in vitro fertilization/intracytoplasmic sperm injection or intrauterine insemination

Abstract: Background: Many studies have suggested that female obesity has an impact on oocyte quality, embryo quality, and endometrial maturation in couples undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). In contrast, there are few data on the management of intrauterine insemination (IUI) in obese women. The objectives of the present study were to evaluate the clinical pregnancy and live birth rates in IVF/ICSI and IUI for overweight or obese women and to determine positive or negative pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
1
Order By: Relevance
“…Hipp [48] reported an increased risk of rst-trimester pregnancy loss after the transfer of frozen embryos compared with fresh embryos in women < 38 y.o, and this difference persisted in women < 30 y.o. This study did not show an impact of BMI on the EPL risk (26.8% of women were overweight and 16% were obese in all cycles), as in our previous study where we did not nd an association between clinical pregnancy and live birth rates and different BMI classes [49]. Similarly, Brunet [50] reported that after adjustment, obesity, including classes II/III, had no impact on EPL rates.…”
Section: Discussioncontrasting
confidence: 43%
“…Hipp [48] reported an increased risk of rst-trimester pregnancy loss after the transfer of frozen embryos compared with fresh embryos in women < 38 y.o, and this difference persisted in women < 30 y.o. This study did not show an impact of BMI on the EPL risk (26.8% of women were overweight and 16% were obese in all cycles), as in our previous study where we did not nd an association between clinical pregnancy and live birth rates and different BMI classes [49]. Similarly, Brunet [50] reported that after adjustment, obesity, including classes II/III, had no impact on EPL rates.…”
Section: Discussioncontrasting
confidence: 43%